2021
DOI: 10.3389/fpsyg.2021.748133
|View full text |Cite
|
Sign up to set email alerts
|

Improving Healthcare Worker Resilience and Well-Being During COVID-19 Using a Self-Directed E-Learning Intervention

Abstract: Introduction: High rates of burnout, depression, anxiety, and insomnia in healthcare workers responding to the COVID-19 pandemic have been reported globally.Methods: Responding to the crisis, the Foundation for Professional Development (FPD) developed an e-learning course to support healthcare worker well-being and resilience. A self-paced, asynchronous learning model was used as the training intervention. Each module included practical, skill-building activities. An outcome evaluation was conducted to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…Research has shown that resilience can act as a “buffer” during high periods of stress and is a protective factor against burnout and post-traumatic stress disorder ( Arrogante and Aparicio-Zaldivar, 2017 ; Kelly et al, 2021 ). During pandemics, there is an opportunity to improve HCWs’ ability to cope with and manage stress by building their resilience as a complementary approach to the necessary systemic efforts required.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that resilience can act as a “buffer” during high periods of stress and is a protective factor against burnout and post-traumatic stress disorder ( Arrogante and Aparicio-Zaldivar, 2017 ; Kelly et al, 2021 ). During pandemics, there is an opportunity to improve HCWs’ ability to cope with and manage stress by building their resilience as a complementary approach to the necessary systemic efforts required.…”
Section: Introductionmentioning
confidence: 99%
“…This study may be compared with other interventional research studies. It is clear from the flurry of recent publications that the mental well-being of HCWs is receiving critical and needed attention, and that mindfulness and coping interventions 4 or more comprehensive wellness interventions 49 are of great interest. Such interventions improve well-being and resilience, 49 but are of considerably longer training duration than CRM.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear from the flurry of recent publications that the mental well-being of HCWs is receiving critical and needed attention, and that mindfulness and coping interventions 4 or more comprehensive wellness interventions 49 are of great interest. Such interventions improve well-being and resilience, 49 but are of considerably longer training duration than CRM. CRM’s strength is its brevity and orientation to the body itself as an in-the-moment tool for stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the conditions, providing mental health programmes for health care workers is urgently needed, both as preventive and curative action (Crittenden, Spieker, & Landini, 2021 ; Yang et al, 2021 ). Besides developing internal ability programmes such as increasing self-efficacy (Vagni et al, 2020 ), resiliency (Kelly, Uys, Bezuidenhout, Mullane, & Bristol, 2021 ), effective appraisal and coping (Cook et al, 2021 ; Ji, Han, Deng, & Lu, 2021 ; Pearman, Hughes, Smith, & Neupert, 2020 ), it is essential to provide social support (Husted & Dalton, 2021 ; Ji et al, 2021 ) and health service such as telecounselling that may feasibly improve mental health conditions (Gupta et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%